The Implications of The Sorogan Method in Increasing Students' Interest and Confidence in Reading The Yellowclassical Book (Kitab Kuning) - Qoriny Abidah Maulidiya; Muhammad Afthon Ulin Nuha (Armala, 2023)
Abstract A good learning method is a method that can increase the interest and ability of students and achieve the planned learning objectives. Teachers must be able to choose and innovate a learning method and make students interested in learning Arabic. In this regard, the sorogan method comes with its techniques and teaching that has intensive closeness with the teacher. Therefore, this study will discuss the description and explanation of the sorogan method in increasing students' interest and confidence. The purpose of this study is to provide results and evidence to people that this sorogan method is effectively used. This research falls into literature study research. Literature research is utilized to obtain research data, namely in the form of sorogan methods to increase students' interest and confidence. The results obtained regarding the technique of this sorogan method, the practice is directly facing the teacher and is assessed directly by the teacher. Keywords: Sorogan Method, Interest and Confidence, Kitab Kuning